Optimization and mechanism of Acid Orange 7 removal by powdered activated carbon coupled with persulfate by response surface method - Wang, Xuxu (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
In this study, powder activated carbon (PAC) utilized to activate peroxydisulfate (PDS) was investigated for decolorization of Acid Orange 7 (AO7). The results indicated a remarkable synergistic effect in the PAC/PDS system. The effect of PAC, PDS dosages and initial pH on AO7 decolorization were studied and the processes followed first-order kinetics. Response surface method with central composite design (CCD) model was utilized to optimize these three factors and analyze the combined interaction. The optimum condition for the decolorization rate of AO7 was analyzed as the following: PAC (0.19 g/L), PDS (1.64 g/L), and initial pH (4.14). Cl- and SO42- showed a promoting effect on AO7 decolorization while HCO3- had a slightly inhibiting effect. Quenching experiments confirmed that both sulfate and hydroxyl radicals were the oxidizing species, and the oxidation reaction occurred on the surface of PAC. The results of UV-vis spectrum with 100% decolorization rate and the 50% total organic carbon reduction indicated highly efficient decolorization and mineralization of AO7 in the PAC/PDS system. Finally, the recovery performance of PAC was studied and the result indicated PAC had poor reuse in reactivity